FIRST REPORT OF TAENIA MUSTELAE (EUCESTODA, TAENIIDAE) PARASITIZING THE BUSHY-TAILED OLINGO, BASSARICYON GABBII (CARNIVORA, PROCYONIDAE) IN SOUTH AMERICAWITH AN UPDATED CHECKLIST OF CESTODES FROM OTHER AMERICAN PROCYONID HOSTS - Magalhães Pinto, Roberto (2009)
The first case of a natural helminth infection with the cestode Taenia mustelae in a specimen of the procyonid Bassarycion gabbii, the bushy-tailed olingo, from the municipality of Barcelos, State of Amazonas, Brazil is reported here. Achecklist of 15 cestode species parasitizing other procyonid hosts in the Americas, between 1958 and 2009 is included in order to update previous data. In the considered period there are no records in Mexico and Central America countries. This is the first report of T. mustelae in South America and B. gabbii is a new host record for this cestode species.